STRATEGI PENINGKATAN LITERASI NUMERASI BERBASIS DIGITAL BAGI GURU SD SESUAI TUNTUTAN KURIKULUM MERDEKA - Lusi Susanti; Nurhizrah Gistituati; Anisah Anisah; Widiawati Widiwati (Universitas Kadiri, 2024)
Numeracy literacy learning is a key component of the independent curriculum and a necessary skill for elementary school students. However, data on low student numeracy literacy, based on the AKM, has been found. Therefore, through a user requirement approach, it is necessary to implement training and mentoring to develop numeracy literacy skills for elementary school teachers to address this issue. The purpose of this activity is to improve teacher numeracy literacy through a digital approach. This PKM activity was carried out by providing training and mentoring to teachers on numeracy literacy. This activity was carried out for all elementary school teachers in Lareh Sago Halaban District, with 35 participants representing each school. This community service activity was well organized. Participants were enthusiastic in every activity. Participants also stated that they gained additional knowledge and new insights from this training activity. The evaluation results showed a positive response from participants to the training, with the percentage of achievement regarding the effectiveness of the training implementation being 90.63%. In terms of participant abilities, there was an increase in participant abilities from 80.58% to 89.09%.